พฤติกรรมการสูบบุหรี่ไฟฟ้าและพฤติกรรมต้องการเลิกบุหรี่ของนักศึกษาระดับอุดมศึกษาในเขตกรุงเทพมหานคร (E-CIGARETTES BEHAVIOR AND SMOKING CESSATION BEHAVIOR OF YOUTH SMOKER IN HIGHER EDUCATION INSTITUTE, BANGKOK) - บุญเพ็ญ ปิยวรรณ; เมนทะระ ภาวนา; บุญเพ็ญ ปิยชาติ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2020)
This research were mix methodology by combines parallel methods. Aims to 1) Study E-cigarettes behavior and smoking cessation behavior of youths smoker. 2) Study causal factors, processes and conditions related to E-cigarettes behavior. Collecting data by questionnaires from 422 smokers and in-depth interview by semi-structured interview from 15 smokers. Analyze data by descriptive statistic, chi-square test and multiple regression in part 1 and content analysis in part 2. and compare, link data of both part to finding the results. Finding were 1) Most E-cigarettes youth smokers were smoke some time by only or meeting with friend. Currently smoking cigarettes by regular cigarettes and E-cigarettes together. They have wanted to quit smoking and try to had smoking cessation but do not succeed. There were 4 variables to predict the electric cigarettes smoking behavior by significantly at level 0.01 that were 1) the persons model of smoking 2) the electric cigarette products 3) the promotion of electric cigarettes and 4) the price of electric cigarettes. The cause of process to entering an electric cigarette cycle were regular smoking experience, seeing person model, receiving propaganda from friends, shop persuasion together with lack the correct knowledge were making them curious to try smoking. However, the electric cigarettes having inferior properties less than regular cigarettes both properties and prices. Most of them return to smoking and are unable to quit smoking.